An abbreviated method for the quality control of pollen counters. Issue 3 (4th May 2019) - Smith, Matt; Oteros, Jose; Schmidt-Weber, Carsten; Buters, Jeroen T M
Abstract: We present an abbreviated method for conducting large scale quality control (QC) exercises over limited time periods, which was used for examining the proficiency of technicians involved in the electronic Pollen Information Network (ePIN). The goal was for technicians to have their analysis skills evaluated at least twice: (1) by having at least one of their slides successfully checked by other counters in the ePIN network and (2) by successfully examining at least one additional slide from other sites. Success was judged as a relative difference (RDif %) ≤ 30% between the two daily average pollen concentrations. A total of 21 sites participated in the ePIN QC exercise. All of the results for total pollen had RDif % < 30%. Only five results had RDif > 30%, three for Betula and two for Poaceae pollen. Of these, three were slides containing < 40 pollen/m 3 daily average and two were for sites that had microscopes with small fields of view and examined < 10% of the slide surface. More than 80% of the participants had at least two slides successfully checked by someone else in the network, and all of the participants had one slide successfully examined. The latter is comparable to a traditional ring test where only one slide is sent to participating sites. The method described here enabled a large number of technicians to be examined in a short period of time and represents a viable alternative to other approaches that can take many months to complete.